2021
DOI: 10.1084/jem.20201353
|View full text |Cite
|
Sign up to set email alerts
|

Platelets orchestrate the resolution of pulmonary inflammation in mice by T reg cell repositioning and macrophage education

Abstract: Beyond hemostasis, platelets actively participate in immune cell recruitment and host defense, yet their potential in the resolution of inflammatory processes remains unknown. Here, we demonstrate that platelets are recruited into the lung together with neutrophils during the onset of inflammation and alongside regulatory T (T reg) cells during the resolution phase. This partnering dichotomy is regulated by differential adhesion molecule expression during resolution. Mechanistically, intravascular platelets fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 83 publications
0
47
0
Order By: Relevance
“…The interaction between platelets and macrophages has not been extensively explored so far. A recent article revealed that in bacteria-induced pulmonary inflammation, platelets educate AMs toward an anti-inflammatory phenotype (featured as CD68 + CD163 + AMs) that mediates remission [125].…”
Section: New Insights Of Platelets In Asthmamentioning
confidence: 99%
“…The interaction between platelets and macrophages has not been extensively explored so far. A recent article revealed that in bacteria-induced pulmonary inflammation, platelets educate AMs toward an anti-inflammatory phenotype (featured as CD68 + CD163 + AMs) that mediates remission [125].…”
Section: New Insights Of Platelets In Asthmamentioning
confidence: 99%
“…Regulatory T (Treg) cells are indispensable for resolution of inflammation ( Hu et al., 2021 ), yet intradermal Treg cells promoted epidermal inflammation in wounded skin by driving keratinocytes to produce neutrophil-recruiting chemokines ( Moreau et al., 2021 ). Platelets helped resolve the pulmonary inflammation associated with bacterial pneumonia in mice by physically trapping Treg cells in the lung and inducing a pro-resolution transcriptional program in macrophages ( Rossaint et al., 2021 ). IgM + B cells adhering within the pulmonary vasculature in the lungs of mice with pneumonitis induced by zymosan or Aspergillus produced lipoxin A4, reducing accumulation of neutrophils ( Podstawka et al., 2021 ).…”
Section: Anti-inflammatory Functions Of Pro-inflammatory Cellsmentioning
confidence: 99%
“…3,4 This binding mediates the adhesion of platelets, leukocytes, T cells, endothelial cells, and tumor cells, resulting in inflammation, thrombosis and tumor growth and metastasis. It is evident that inhibiting the binding between P-selectin and PSGL1 sheds light on drug development for treating inflammation, 5 arterial thrombosis, 6 venous thrombosis, 7 tumor growth, 8 tumor metastasis, 8 and cancer-associated thrombosis. [9][10][11] Currently, drugs designed for this purpose mainly fall into three types: monoclonal antibodies, including inclacumab 12 and crizanlizumab, 13 glycosulfopeptides mimicking truncated N-terminal PSGL1 monomers like GSnP-6, 14 and small-molecule inhibitors, such as GMI-1070, 15 bimosiamose (TBC1269), 16 and PSI-697.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 This binding mediates the adhesion of platelets, leukocytes, T cells, endothelial cells, and tumor cells, resulting in inflammation, thrombosis and tumor growth and metastasis. It is evident that inhibiting the binding between P-selectin and PSGL1 sheds light on drug development for treating inflammation, 5 arterial thrombosis, 6 venous thrombosis, 7 tumor growth, 8 tumor metastasis, 8 and cancer-associated thrombosis. 9–11 …”
Section: Introductionmentioning
confidence: 99%